What Matters Most Is How Well You Walk Through the Fire - Bukowski, Charles (Santa Rosa, CA : Black Sparrow Press, 1999)
What Matters Most Is How Well You Walk Through the Fire is the second posthumous collection from Charles Bukowski that takes readers deep into the raw, wild vein of writing that extends from the early 1970s to the 1990s.